A study of poplar organosolv lignin after melt rheology treatment as carbon fiber precursors. Issue 18 (16th June 2016) - Sun, Qining; Khunsupat, Ratayakorn; Akato, Kokouvi; Tao, Jingming; Labbé, Nicole; Gallego, Nidia C.; Bozell, Joseph J.; Rials, Timothy G.; Tuskan, Gerald A.; Tschaplinski, Timothy J.; Naskar, Amit K.; Pu, Yunqiao; et al.
Abstract : Poplar organosolv lignins were investigated for structural changes after rheology treatment as a carbon fiber precursor. Abstract : Lignins from various poplar genotypes were isolated by using organosolv fractionation and subjected to rheological treatment at various temperatures. Physicochemical characterization of the lignin variants shows a broad distribution of glass transition temperatures, melt viscosity, and pyrolysis char residues. Rheological treatment at 170 °C induces lignin repolymerization accompanied with an increase in condensed linkages, molecular weights, and viscosities. In contrast, rheology testing at 190 °C results in the decrease in lignin aliphatic and phenolic hydroxyl groups, β-O-aryl ether linkages, molecular weights, and viscosity values. Lignin under air cooling generates more oxygenated and condensed compounds, but lower amounts of ether linkages than lignin cooled under nitrogen. Lignin with a lower syringyl/guaiacyl ratio tends to form more cross-linkages along with higher viscosity values, higher molecular weight and larger amounts of condensed bonds.